Three women disappear [compact disc, unabridged] - Patterson, James, 1947-; Serafin, Shan, 1982- (Hachette Audio, 2020)
When a rich stockbroker is found dead, the police deem it suicide. Until suspicious facts start to point the finger at three women, who have all gone missing.